Generation of Oxygen Free Radicals by Proflavine: Implication in Protein Degradation - Mansour K.M. Gatasheh; Kannan Subbaram; Hemalatha Kannan; Imrana Naseem (HAYATI Journal of Biosciences, 2017)
Proflavine, an acridine dye, is a known DNA intercalating agent. In the present study, we show that proflavine alone on photoillumination can generate reactive oxygen species (ROS). These proflavine-derived ROS cause damage to proteins, and this effect is enhanced when the divalent metal ion Cu (II) is included in the reaction. Bathocuproine, a specific Cu (I) sequestering agent, when present in the reaction mixture containing Cu (II), was found to inhibit the protein degradation, showing that Cu (I) is an essential intermediate in the reaction. The effect of several scavengers of ROS such as superoxide dismutase, sodium azide, potassium iodide, and thiourea were examined on the protein damaging reaction. Potassium iodide was found to be the most effective in inhibiting protein damage followed by sodium azide and thiourea. Our results indicate the involvement of superoxide, singlet oxygen, triplet oxygen, and hydroxyl radicals in proflavine-induced damage to proteins.